Effect of irrigation and pruning on the fog capture ability of Chilean xerophytic formations - Cuevas, Jaime G.; Ostria-Gallardo, Enrique; Hernández, Pedro; Bustamante, Catalina; Acuña, Rodrigo (Bosque (Valdivia), 2025)
Water availability and herbivory are critical factors limiting plant growth in semi-arid regions. Xerophytes in fog ecosystems, while capable of capturing fog water, are likely constrained by these factors. Given that fog capture is closely tied to vegetation structure in terms of canopy volume, cross-section, and leaf traits, we hypothesized that irrigation and pruning (as a form of controlled herbivory) could enhance fog harvest by stimulating canopy growth. To test this, we evaluated the impact of these management practices on ten xerophytic species across two communities in north-central Chile. We assessed plant responses through cross-sectional growth, branch elongation, and fog drip beneath the canopy. Irrigation promoted cross-sectional growth in two species, while pruning negatively impacted three species. In terms of branch growth, two species responded positively to irrigation, while one was negatively affected by pruning. Fog drip analysis revealed significant treatment effects in less than 11% of species × site × treatment × time combinations, with negative effects prevailing. Interactions between treatments sometimes nullified or altered their effects, indicating that irrigation is necessary for pruning impacts to manifest. As pruning consistently led to negative outcomes, we suggest that intense herbivory may similarly impair shoot growth and fog collection. Overall, our findings indicated that xerophytes do not require irrigation or pruning to sustain their fog capture potential. However, irrigation enhanced growth and vigor in several species, suggesting its potential utility in productive or restoration contexts, particularly when management practices are tailored to species- specific responses.